Efficiency of some Common Coatings in Controlling Water Vapour Absorption by Wood Substrate - Gupta, Sachin; Shukla, Shikhar; Kishan Kumar, V. S. (Indian Forester, 2016)
The efficiency of four common wood coatings was investigated in this study on Melia dubia wood substrate. The per cent weight gain of coated samples and the per cent increment over initial moisture contents of the coated samples were compared. It is found that Lacquer and NC lacquer coated samples gave the least increments in MC after 25 days of exposure to high humidity. Lacquer coated samples resulted in only half Per cent weight gain compared to uncoated samples in the same duration. Though all the coating showed high MEE values in the beginning of the experiment, only the two lacquer coatings could retain 45-56%of their initial MEE values.Melamine and PU coated samples could retain only 9-16%. The water vapour transmission rates of Lacquer and Nitrocellulose lacquer coated samples also exhibited minimum values. The study illustrated the superiority of lacquer and NC lacquer in restricting moisture entry into M.dubia wood substrate.